SISTEM DETEKSI DINI BANJIR BERBASIS SENSOR FLOAT MAGNETIC LEVEL GAUGE - Fahrul Fahrul; Miranty Miranty; Ambo Asse; Yuli Asmi Rahman (Foristek, 2013)
Central Sulawesi has tropical climate conditions with interconnected rivers caused each of it can experience the impact of the sudden rise of water levels if there is a heavy rainfall in upstream areas which is commonly called “a sent flood”. Therefore, it is needed an early detector flood tool that works based on the height of river water level so that the impact of floods can be minimized. Early detector flood tool can function automatically by giving early warning when water levels reach a certain limit. The detector of height levels of river streams is designed using float magnetic level gauge method. This height level of river streams detector is able to provide information in real time based on the height level of river streams by giving information in the form of warning light indicator and siren alarm as alert and danger sign.